The family in early modern England - Berry, Helen, 1969-; Foyster, Elizabeth A., 1968- (Cambridge University Press, 2007)
With an appeal to scholars of early modern British history, social history, family history and gender studies, this work sheds light on family ideals and experiences in the early modern period. It features contributions by distinguished historians of family life and a new generation of historians working in the field.